Sistem angka perpuluhan yang diketahui tertua di dunia: angka Malayonesia - Shaharir bin Mohamad Zain (Tanjong Malim, 2019)
Sistem angka perpuluhan yang diketahui tertua di dunia: angka Malayonesia by Shaharir bin Mohamad Zain